Production of [89Zr]Oxinate4 and cell radiolabeling for human use. (19th January 2021) - Massicano, Adriana V.F.; Bartels, Jennifer L.; Jeffers, Charlotte D.; Crenshaw, Bryant K.; Houson, Hailey; Mueller, Christina; Younger, Jarred W.; Knapp, Paul; McConathy, Jonathan E.; Lapi, Suzanne E.
Abstract : [ 89 Zr]Oxinate4 is a Positron Emission Tomography (PET) tracer for cell radiolabeling that can enable imaging techniques to help better understand cell trafficking in various diseases. Although several groups have synthetized this compound for use in preclinical studies, there is no available data regarding the production of [ 89 Zr]Oxinate4 for human use. In this report, we describe the detailed production of [ 89 Zr]Oxinate4 under USP <823> and autologous leukocyte radiolabeling under USP <797>. The final product presented high radiochemical purity and stability at 24 h post synthesis (>99%) and passed in all quality control assays required for clinical use. [ 89 Zr]Oxinate4 did not compromise the white blood cells viability and did not show considerable cellular efflux up to 3 h post labeling. The translation of this technique into human use can provide insight into several disease mechanisms since [ 89 Zr]Oxinate4 has the potential to label any cell subset of interest. Abstract : In this work, we described the production of [ 89 Zr]Oxinate4 under USP <823> regulations and radiolabeling of autologous leukocyte under USP <797> which make the final product suitable for clinical use.